Molecular Reconstruction Method Based on NIR Spectroscopy for Reformates - Cheng, Mingyuan; Zhang, Linzhou (Energies (Basel), 2023)
With the increasing attention to environmental protection and strict national standards, the production of high-quality clean gasoline is more and more required in modern refineries. At present, the molecular-level online modeling of the gasoline blending process is rarely reported due to the lack of a proper characterization method. In this study, we have developed a molecular reconstruction method based on near-infrared (NIR) spectroscopy. We established a library that comprises an NIR spectrum and molecular composition of known reformates. We developed the sample selection algorithm that finds the sample with an NIR spectrum close to the target sample. The method-solving algorithm based on multiple linear regression was used to obtain the molecular composition of gasoline quickly. The method combines online measurement methods and molecular management technology to achieve online composition reconstruction. Seventy-five groups of reformates were collected to verify the feasibility of the method, and the results showed that the method predicted well.